Carboplatin therapeutic monitoring in preterm and full-term neonates. Issue 14 (September 2015) - Veal, Gareth J.; Errington, Julie; Hayden, James; Hobin, David; Murphy, Dermot; Dommett, Rachel M.; Tweddle, Deborah A.; Jenkinson, Helen; Picton, Susan
Abstract: Introduction: Administration of the most appropriate dose of chemotherapy to neonates is particularly challenging and frequently not standardised based on any scientific rationale. We report the clinical utility of carboplatin therapeutic drug monitoring in preterm and full-term neonates within the first month of life. Methods: Carboplatin therapeutic monitoring was performed to achieve target drug exposures area under the plasma concentration–time curve (AUC values) in nine preterm and full-term neonates diagnosed with retinoblastoma or neuroblastoma treated over an 8 year period. Carboplatin was administered over 3 days with therapeutic drug monitoring utilised to target cumulative AUC values of 5.2–7.8 mg/ml min. Results: AUC values achieved were within 15% of target values for the individual courses of treatment in all but one patient (12/13 courses of treatment), with dose modifications of up to 215% required to achieve target AUC values, based on initial mg/kg dosing schedules. Carboplatin clearance determined across three consecutive chemotherapy courses in two patients increased from 3.4 to 7.1 ml/min and from 7.2 to 16.5 ml/min, representing increases of 210–230% over several weeks of treatment. Complete remission was observed in 8/9 patients, with no renal toxicity reported and only one patient experiencing ototoxicity. Conclusion: The study highlights the benefits of utilising therapeutic drug monitoring to achieve target carboplatin AUC values in preterm and full-term neonates treated within the first few weeks of life, particularly in view of marked increases in drug clearance observed over consecutive chemotherapy courses. In the absence of therapeutic drug monitoring, body-weight based dosing is recommended, with dosing guidance provided for both approaches to inform future treatment.